KAJIAN NORMATIF PUTUSAN MAHKAMAH KONSTITUSI NOMOR.21/PUU-XIII/2020 TENTANG HAK TANGGUNGAN ATAS TANAH - MASYHUR MASYHUR; RIZQI YANIPASI APRIYANDI (GANEC SWARA, 2022)
The purpose of this study is to find out the considerations of the constitutional court to reject the applicant's application based on Law No. 4 of 1996 and the position of the evidence submitted by the applicants in case No. 21/PUU-XVIII/2020 (Evidence P-4,P-5, and P-7). This research is a normative research by analyzing or reviewing a valid and competent statutory regulation to be used as a basis for problem solving.Case Number 21/PUU-XVIII/2020 which is considered by the judges of the Constitutional Court is that there is no agreement between the debtor and the creditor in which there is no clause on breach of contract and there is an overmacht/force majeure in the agreement, as stipulated in Article 1865 of the KUH Civil law, but in this case it is not included because the applicant has never included a court decision regarding coercion and breach of contract in accordance with Law Number 4 of 1996 concerning Mortgage Article 20 paragraph (1) and Article 14 paragraph (3) of the Mortgage Law, so that the judges of the Constitutional Court rejected the petitioners' petition. In Case Number 21/PUU-XVIII/2020 there is evidence that forms the basis or corroboration of the arguments of the petitioners' petition as for the position of the evidence submitted as follows an explanation of the debtor and creditor agreements, Land Rights Certificates and Mortgage Certificates, Analysis of the decision of N. 18/puu-xvii/2019, the implications of the Constitutional Court's decision No.18/PUU-XVII/2019 on the community and all evidence submitted by the applicant is not in accordance with applicable legal provisions. All evidence submitted by the applicant is clear that the debtor or applicant has not suffered a loss so that the position of the evidence is not in accordance with the applicable legal provisions